Development Of Recombinant Mycobacterium Bovis Bacille Calmette Guerin (Rbcg) Expressing The 19 Kda C-Terminus Of Merozoite Surface Protein-1 (MSP-1C) And The 22kda Of Serine Repeat Antigen (SE22) Of Plasmodium Falciparum As A Potential Blood-Stage Malarial Vaccine [QR82.M8 N974 2008 f rb]. - Abdullah, Nurul Asma (2008)
Mycobacterium bovis bacille Calmette–Guerin rekombinan (rBCG) yang mengekspres terminus C protein permukaan merozoit-1 19kDa (MSP-1C)